Do Small Social Wasp Colonies Defend Against Large Intruders? - Christopher K Starr; Craig A. Western; Aidan D. Farrell (Sociobiology)
Against the hypothesis that the ability to defend the brood by stinging is a key enabling mechanism in the origin of sociality in the Hymenoptera, it was claimed that small colonies do not defend the nest against large adversaries. We report on a test of this claim. Using a simulated vertebrate intruder, we provoked early colonies of three species of paper wasps (Polistes) until all adult females had either attacked or fled. In each species, a substantial fraction of adult females attacked the intruder, with an approximately linear relationship between the total number of females and the number attacking, consistent with the initial hypothesis. This experimental approach also presents a novel method for comparing attack-readiness between species, developmental stages, or experimental conditions.